Evaluation of cherry tomato hybrids cultivated in pots and with different stem conditions (Research, Society and Development, 2020)
The cherry tomatoes (Lycopersicon esculentum var. cerasiforme), with firmer fruits and smaller size, of color orange, yellow or red, has attracted customers from different classes looking for a differentiated product. The objective of this study was to evaluate the performance of hybrids of tomato cultivation in pots in greenhouse under the conditions of the Lower Basin of the São Francisco Valley. The fruits used in the assay were obtained from the experiment conducted at the experimental field of the DTCS /UNEB, in Juazeiro / BA. The experimental design was randomized blocks in split plot scheme of type 5 x 2 x2 with three replicates and six plants per plot. Treatments consisted of five different hybrids of tomato; pot of 5 and 7 liters and different conduction rods. The plots were hybrids of tomato and the subplots of pot sizes and types of pruning, arranged randomly in the plots. The evaluations were production, post-harvest (physico-chemical - AT, SS, ratio) and sensory. It was observed that it is possible to obtain the fruits of tomato hybrids weekly with quality for consumption, which demonstrates the ability of tomato production under the conditions of the Lower Basin of the São Francisco Valley. The pots l of 5 liters is recommended for cultivation the cherry tomatoes under management conditions of fertigation. The realization of pruning did not affect yield components and did not affect fruit quality.